Dissemination of information on Management of pesticides to rural farmers in Oyo state, Nigeria (2000)
This study discovered that advance information on the positive aspect of pesticides is till scare to the Agricultural extention workers especially technical journals in Nigeria. It is essential that those involved with pesticides, in their use, regualtion or production and distribution should have ready access to up-to- date information. If information on pesticides is not available, resources be wasted, the health of human and livestock may be at risk and environment disasters may occur.